Konstruksi semantis kata pada perkembangan bahasa Indonesia anak - Sukartiningsih, Wahyu (citeus, 2010)
The aim of this study is to determine the semantic construction in Indone- sian language by pre-school-age children. The present research consisted of a longitudinal study of five pre-school-age children. The study of these five children is based on the developmental psycholinguistic and semantic-pragmatic studies. To collect the data, we used the observation, recording, and interview technique. The results show that the semantic construction of word meaning in Indonesian language by pre-school-age children consisted of: (1) over-specification, (2) overgeneraliza- tion, (3) intersection, (4) towards meaning spesification, and (5) meaning associa- tion. Overgeneralization and intersection dominated language development by child- ren in 2 until 4 year olds, even though since 4 year old those indications are decreasing.